2006
DOI: 10.1073/pnas.0603780103
|View full text |Cite
|
Sign up to set email alerts
|

Collective evolution and the genetic code

Abstract: A dynamical theory for the evolution of the genetic code is presented, which accounts for its universality and optimality. The central concept is that a variety of collective, but non-Darwinian, mechanisms likely to be present in early communal life generically lead to refinement and selection of innovation-sharing protocols, such as the genetic code. Our proposal is illustrated by using a simplified computer model and placed within the context of a sequence of transitions that early life may have made, before… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
371
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 324 publications
(393 citation statements)
references
References 29 publications
15
371
0
1
Order By: Relevance
“…Moreover, although Darwin did not use the term neutral evolution, he acknowledged that evolutionary change can involve fixation of variants that confer no selective advantage over previous adaptations; nevertheless, neutral evolution is commonly referred to as non-Darwinian [70,75,123]. Similarly, although Darwin was not committed to the idea that all life evolved from a single common ancestor, processes such as horizontal gene transfer (that is, genes transmitted between organisms in a manner other than through traditional reproduction) are commonly referred to as non-Darwinian [131]. Finally, the existence of non-Darwinian processes does not negate the feasibility of Darwinian ones, and vice versa.…”
Section: Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, although Darwin did not use the term neutral evolution, he acknowledged that evolutionary change can involve fixation of variants that confer no selective advantage over previous adaptations; nevertheless, neutral evolution is commonly referred to as non-Darwinian [70,75,123]. Similarly, although Darwin was not committed to the idea that all life evolved from a single common ancestor, processes such as horizontal gene transfer (that is, genes transmitted between organisms in a manner other than through traditional reproduction) are commonly referred to as non-Darwinian [131]. Finally, the existence of non-Darwinian processes does not negate the feasibility of Darwinian ones, and vice versa.…”
Section: Terminologymentioning
confidence: 99%
“…Subsequently von Neumann showed that the minimal algorithmic structure capable of evolving through natural selection is a self-assembly code that gets used in two distinct ways [131]. First, it is actively deciphered (by what he referred to as the constructor) to construct a new automaton, a highly self-similar replicant of itself.…”
Section: The Algorithmic Structure Of Natural Selectionmentioning
confidence: 99%
See 3 more Smart Citations